The efficacy of frames in a persuasion paradigm : an exploratory examination of the role of information background. - Tan, Kai Foong. (2009)
Within the persuasion paradigm, studies assessing the efficacy of positively (gain-framed) or negatively (loss-framed) framed messages have shown the negative frame to be more persuasive than positive frame (Ganzach & Karsahi, 1995; Martin, 1993; Meyerowitz & Chaiken, 1987). This is largely true of studies utilizing the "benefits gained and benefits foregone" approach of operationalizing frames. There is ample evidence on the phenomenon of "negativity bias"- the tendency to weigh, give more attention and consideration to negative information in judgment and choice, in information integration and impression formation research [see Kanouse (1984) for a review]. One of the hypotheses proposed to explain this effect is the figure-ground hypothesis. This hypothesis states that negative information is more salient and distinctive than positive information in a world perceived by people to be generally positive (Kanouse & Hanson, 1972). Because there is generally a positivity bias in our perceptions of the world, the negative information effect is observed. In the same vein, Lutz (1975) argues, on the basis of Brock's commodity theory, that negative information is more potent than positive because of its relative scarcity and novelty. This increases the probability that it should be attended and remembered (Fiske, 1980).